The World Bank policy on access to information (The World Bank, 2010)
The World Bank Policy on Access to Information sets forth a groundbreaking change in how the World Bank makes information available to the public. Now the public can get more information than ever before—information about projects under preparation, projects under implementation, analytic and advisory activities, and Board proceedings.